Proficiency of European GMO control laboratories to quantify MON89788 soybean in a meat pâté matrix. (March 2023) - Broothaerts, W.; Beaz Hidalgo, R.; Buttinger, G.; Seghers, J.; Maretti, M.; Robouch, P.; Corbisier, P.
Abstract: GMO control laboratories in the EU routinely monitor the presence and content of genetically modified organisms (GMOs) in food and feed products collected from the EU market. As the vast majority of GMOs comprize genetically modified plants, most control samples have a plant-based origin. For the first time, a pilot proficiency test was organised requiring the analysis of GMOs in a meat matrix. Meat pâté, a product in which soybean is occasionally identified, was spiked with GM soybean event MON89788, homogenised by mixing, aliquoted in sachets and frozen. The assigned value was determined by two independent expert laboratories. Several DNA extraction methods were tested and proved to be insufficient for the removal of PCR inhibitors present in the DNA extracts, resulting in a GM content underestimated by at least 30%. This problem was solved either by using hot-start qPCR chemistry or by applying the same method in a digital PCR format. A total of 52 laboratories participated in the study. They were requested to verify the presence of any GM soybean in the test item and to quantify the GM event(s) identified by their method of choice. All but one laboratory identified the MON89788 soybean event present in the pâté matrix. The majority of the quantitative results reported were below the assigned value, but did not deviate more than 50% from it. This study demonstrated the proficiency of most GMO control laboratories for the analysis of GMOs in a meat-based product. It also shows that method optimisation for GMO analysis in meat products is nevertheless advisable. Highlights: DNA extraction from meat-based materials cannot completely remove PCR inhibitors. PCR inhibition is alleviated by use of either hot-start qPCR or droplet digital PCR. EU control laboratories are competent for GMO analysis in meat-based products.